Preliminary study on age- and sex-dependent alterations in the composition of skeletal muscle fibers of Brasileiro de Hipismo horses - D'Angelis, Flora H. F. [UNESP]; da Silva, Marco A. G. [UNESP]; Albernaz, Raquel M. [UNESP]; Ferraz, Guilherme C. [UNESP]; Boleli, Isabel C. [UNESP]; Lacerda-Neto, Jose C. [UNESP]; Ademir de Oliveira, Joao [UNESP]; Oliveira, Jose V.; Queiroz-Neto, Antonio [UNESP] (Elsevier B.V., 2008)
The aim of this work was to characterize the distribution of myofibers in the gluteus medius muscle of inactive horses of the Brasileiro de Hipismo (BH) breed at different ages by means of histochemical analyses, according to sex and depth of the biopsy. A total of 78 inactive horses (9 castrated males, 35 stallions, and 34 females) of the BH breed, aged 1 to 4 years, were used. A percutaneous muscle biopsy was obtained with a 6.0-mm Bergstrom-type needle, which allowed the removal of muscle fragments at depths of 20 and 60 mm. Myofiber types were determined based on myofibrillar adenosine triphosphatase (mATPase) and nicotinamide dinucleotide tetrazolium reductase (NADH-TR) techniques. Morphometry of the fibers was determined based on cross-sectional area (CSA), mean frequency (F), and relative cross-sectional area (RCSA). The current study demonstrated that BH horses 3 and 4 years of age show a greater percentage of, and area occupied by, type IIA fibers and lower percentage of type IIX fibers in the gluteus medius muscle compared with horses 1 and 2 years of age. No difference was found between sexes in the frequency of and area occupied by the different fiber types at any of the depths and ages studied. In this study, females showed a greater CSA for all fibers in comparison with males, at 1 year of age. The results of the current study indicate that the gluteus medius muscle of inactive BH horses shows modifications in its structural and biochemical composition during the growth of the animals, leading to a better oxidative capacity.
Keywords: muscle adaptions; Gluteus medius muscle; Horse; histochemical